Air-stable aryl derivatives of pentafluoroorthotellurate. Issue 69 (12th August 2022) - Wegener, Daniel; Hoffmann, Kurt F.; Pérez-Bitrián, Alberto; Bayindir, Ilayda; Hadi, Amiera N.; Wiesner, Anja; Riedel, Sebastian
Abstract : The synthesis of air-stable aryl derivatives of OTeF5  has been achieved through the use of convenient procedures. Pentafluorophenyl derivatives are stronger acids and more robust against electrophiles in comparison to phenyl analogues. Abstract : We report on two different sets of air-stable derivatives of pentafluoroorthotellurate containing fluorinated and non-fluorinated aryl groups. The acid cis -PhTeF4 OH was obtained in gram scale and further transformed to Ag[ cis -PhTeF4 O], which was used as a cis -PhTeF4 O transfer reagent to obtain [PPh4 ][ cis -PhTeF4 O]. Furthermore, the synthesis of trans -(C6 F5 )2 TeF3 OH was achieved by a selective hydrolysis of trans -(C6 F5 )2 TeF4 in the presence of KF and subsequent protonation by a HF. Quantum-chemical calculations show a higher acidity and robustness against fluoride abstraction for trans -(C6 F5 )2 TeF3 OH compared to cis -PhTeF4 OH.